Zinc‐Ion Batteries: Multi‐Scale Investigations of δ‐Ni0.25V2O5·nH2O Cathode Materials in Aqueous Zinc‐Ion Batteries (Adv. Energy Mater. 15/2020). Issue 15 (21st April 2020) - Li, Jianwei; McColl, Kit; Lu, Xuekun; Sathasivam, Sanjayan; Dong, Haobo; Kang, Liqun; Li, Zhuangnan; Zhao, Siyu; Kafizas, Andreas G.; Wang, Ryan; Brett, Dan J. L.; Shearing, Paul R.; et al.
Abstract : In article number 2000058, Guanjie He, Ivan P. Parkin and co‐workers report the synthesis of δ‐Ni0.25 V2 O5 materials as aqueous zinc‐ion battery cathodes. The materials and electrodes undergo investigation from molecular, nanoscale to the microscopic scale. The cathode material shows best in class capacity (402 mAh g −1 at 0.2 A g −1 ) and stability (a capacity retention of 98% over 1200 cycles at 5 A g −1 ).